2003
DOI: 10.4049/jimmunol.171.11.5842
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell-Induced Activation of Adaptive and Innate Antitumor Immunity

Abstract: While studying Ag-pulsed syngeneic dendritic cell (DC) immunization, we discovered that surprisingly, unpulsed DCs induced protection against tumor lung metastases resulting from i.v. injection of a syngeneic BALB/c colon carcinoma CT26 or a syngeneic C57BL/6 lung carcinoma LL/2. Splenocytes or immature splenic DCs did not protect. The protection was mediated by NK cells, in that it was abrogated by treatment with anti-asialo-GM1 but not anti-CD8, and was induced by CD1−/− DCs unable to stimulate NKT cells, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
74
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 57 publications
(49 reference statements)
6
74
0
Order By: Relevance
“…The DC-based immunotherapy was optimized by providing a potent microbial stimulus of whole bacteria and our results confirm those of others showing that NK cells and IFN-g are required for optimal DC based therapy (17,18,23).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The DC-based immunotherapy was optimized by providing a potent microbial stimulus of whole bacteria and our results confirm those of others showing that NK cells and IFN-g are required for optimal DC based therapy (17,18,23).…”
Section: Discussionsupporting
confidence: 76%
“…3B). In contrast, some studies have demonstrated that immunization with syngenic DC alone (in the absence of tumor Ag) can induce NK cell-dependent antitumor responses against melanoma, colon, or lung carcinoma (17,20,23). We have previously noted that immunization with syngenic DC in the absence of tumor Ag can induce antimelanoma immunity in the prophylactic setting, but only if FCS Ags are present in both the DC and the melanoma culture medium (37,39).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For prolonged periods (up to 12 months), the immunized mice have NKT and NK cells that are in a ''primed'' state, being able to produce IFN-g rapidly upon challenge with B16 melanoma and to resist the metastases of B16 to the lung. After we had performed our experiments, we became aware of two publications that reported long-term NK-based resistance induced by DC vaccines [12,13]. Our paper extends this prior research in three ways: (i) by comparing DC Figure 5.…”
supporting
confidence: 50%